Mathematical modeling of bulk material batching - Коваленко, Ігор Валентинович; Янцибаєв, Дмитро Сергійович (Technology audit and production reserves, 2016)
The authors conducted mathematical modeling of the moving process of bulk material from the hopper of the linear weight butcher in receiving working body of the feeder. 5 typical areas of structural and mechanical condition of bulk material during its bulking from the discharge channel in the side of the bunker were considered. Formula describing the speed of material bulking was developed. Formulas that describe the thickness of the layer of bulking material on the feeder of linear butcher and the required speed of movement to maintain this thickness were developed too. The butcher reached maximum speed providing matching of bulk material bulking from the discharge bunker channel and intensity of its movement on the supporting body of the feeder. To solve this problem it was conducted simulation of the intensity curve of moving process of bulk material using MATLAB software. The article will be interest to designers, engineers and scientists who conduct research in the development and improvement of weight butchers. Also, the article will be useful for graduate students and senior students of relevant specialties.